Manganese Silylene Hydride Complexes: Synthesis and Reactivity with Ethylene to Afford Silene Hydride Complexes. Issue 22 (15th March 2017) - Price, Jeffrey S.; Emslie, David J. H.; Britten, James F.
Abstract: Reaction of the ethylene hydride complex trans ‐[(dmpe)2 MnH(C2 H4 )] (1 ) with Et2 SiH2 at 20 °C afforded the silylene hydride [(dmpe)2 MnH(=SiEt2 )] (2 a ) as the trans ‐isomer. By contrast, reaction of1 with Ph2 SiH2 at 60 °C afforded [(dmpe)2 MnH(=SiPh2 )] (2 b ) as a mixture of the cis (major) and trans (minor) isomers, featuring a Mn‐H‐Si interaction in the former. The reaction to form2 b also yielded [(dmpe)2 MnH2 (SiHPh2 )] (3 b ); [(dmpe)2 MnH2 (SiHR2 )] (R=Et (3 a ) and Ph (3 b )) were accessed cleanly by reaction of2 a and2 b with H2, and the analogous reactions with D2 afforded [(dmpe)2 MnD2 (SiHR2 )] exclusively. Both2 a and2 b engaged in unique reactivity with ethylene, generating the silene hydride complexes cis ‐[(dmpe)2 MnH(R2 Si=CHMe)] (R=Et (4 a ), Ph (4 b )). Compounds trans ‐2 a, cis ‐2 b, 3 b, and4 b were crystallographically characterized, and bonding in2 a, 2 b, 4 a, and4 b was probed computationally. Abstract : Alkene hydride complex trans ‐[(dmpe)2 MnH(C2 H4 )] eliminates ethane upon reaction with secondary silanes, yielding cis ‐ and trans ‐isomers of the silylene hydride complexes [(dmpe)2 MnH(=SiR2 )]. Reaction with ethylene yields silene hydride complexes [(dmpe)2 MnH(R2 Si=CHMe)]—most likely via a low‐coordinate silyl isomer [(dmpe)2 Mn(SiHR2 )] that is in equilibrium with the silylene hydrides.